The Role of Digital Transformation and Entrepreneurial Orientation in Achieving Competitive Advantage in Industry 4.0: A Study of Digital Transformation on Non-Banking Organizations in Indonesia - Alanudin, Dian (CV. Publikasi Indonesia, 2024)
In the realm of transitioning economies and the advent of Industry 4.0, digital transformation has emerged as a paramount subject. Nonetheless, there remains a scarcity of studies offering a comprehensive elucidation of the interplay between Digital Transformation (DT) and Entrepreneurial Orientation (EO) in the context of Organizational Change (OC). Digital transformation entails the integration of digital technology across all facets of business operations, fundamentally altering how enterprises function and deliver value to clientele. This paper explores these dynamics by addressing three fundamental inquiries: Firstly, how do digital transformation and entrepreneurial orientation correlate with the Organizational Change (OC) process? Secondly, why are digital transformation and entrepreneurial orientation deemed pivotal? Lastly, how do digital transformation and entrepreneurial orientation impact Organizational Change, and do they influence innovation behaviour and competitive advantage? This paper aims to enrich the discourse and foster an understanding of the critical roles played by digital transformation and entrepreneurial orientation in attaining competitive advantage through the Organizational Change (OC) process and fostering innovation behaviour at PT Pegadaian. To bridge the existing gap in the literature, this study posits digital transformation and entrepreneurial orientation as antecedents of the Organizational Change (OC) process, thereby fostering innovation behaviour and competitive advantage. The research adopts a case study approach rooted in qualitative analysis.